Effects of endplate coverage and intervertebral height change on heterotopic ossification following cervical disc replacement - Yi-Wei Shen (BMC, 2021)
Abstract Background Heterotopic ossification (HO) is a common complication after cervical disc replacement (CDR). Biomechanical factors including endplate coverage and intervertebral disc height change may be related to HO formation. However, there is a dearth of quantitative analysis for endplate coverage, intervertebral height change and their combined effects on HO. Methods Patients who underwent single-level or two-level CDR with Prestige-LP were retrospectively reviewed. Clinical outcomes were evaluated through Japanese Orthopaedic Association (JOA) score, Neck Disability Index (NDI) score, and visual analogue scale (VAS) score. Radiological data, including the prosthesis-endplate depth ratio, intervertebral height change, posterior heterotopic ossification (PHO) and angular parameters, were collected. Logistic regression analysis was used to identify the potential risk factors. Receiver operating characteristic curves were plotted and the cut-off values of each potential factors were calculated. Results A total of 138 patients with 174 surgical segments were evaluated. Both the prosthesis-endplate depth ratio (P < 0.001) and post-operative disc height change (P < 0.001) were predictive factors for PHO formation. The area under the curve (AUC) of the prosthesis-endplate depth ratio, disc height change and their combined effects represented by the combined parameter (CP) were 0.728, 0.712 and 0.793, respectively. The risk of PHO significantly increased when the prosthesis-endplate depth ratio < 93.77% (P < 0.001, OR = 6.909, 95% CI 3.521–13.557), the intervertebral height change ≥ 1.8 mm (P < 0.001, OR = 5.303, 95% CI 2.592–10.849), or the CP representing the combined effect < 84.88 (P < 0.001, OR = 10.879, 95% CI 5.142–23.019). Conclusions Inadequate endplate coverage and excessive change of intervertebral height are both potential risk factors for the PHO after CDR. Endplate coverage less than 93.8% or intervertebral height change more than 1.8 mm would increase the risk of PHO. The combination of these two factors may exacerbate the non-uniform distribution of stress in the bone-implant interface and promote HO development.